Model of Islamic Governance and Judicial Independence: A Study of the Separation of Powers in the Era of Khulafaur Rasyidin - Bani Adam I'tishan; Ahmad Zulkifli Affandi; Abdul Halim Talli; Asni Asni (Publikasi Indonesia, 2025)
The separation of powers is a fundamental principle for ensuring justice and preventing the abuse of authority within a governance system. In the context of Islamic history, particularly during the Rashidun Caliphate, the need to distinguish between executive and judicial authority emerged as essential to uphold legal integrity and the rule of justice. This study aims to analyze the early development (embryo) of the separation of powers during the Rashidun era, identify the socio-historical factors that influenced it, and evaluate its impact on the effectiveness and integrity of the Islamic judicial system. This research employs a socio-historical approach, utilizing content analysis of classical Islamic texts and historical documents, as well as historical comparison of governance practices of the period. The findings indicate that the institutionalization of judicial independence began under the leadership of Caliph Umar ibn al-Khattab through the appointment of independent qadis, provision of stable salaries, and the establishment of judicial oversight mechanisms. Factors such as urbanization, territorial expansion, increasing societal complexity, and the need for administrative efficiency were central to these reforms. The study concludes that the separation of powers in the Rashidun era was not only a pragmatic solution to governance challenges but also a reflection of core Islamic principles of justice. This historical model offers a valuable precedent for strengthening judicial independence and ethical governance, and remains relevant as a reference for contemporary judicial reform in Muslim-majority societies.